The Effect of Variety and Harvesting Time of Sorghum Planted in Stylosanthes Pasture on Growth, Production and Prussic Acid Content - Meita Puspa Dewi; Nafiatul Umami; Bambang Suhartanto (Buletin Peternakan, 2019)
This research was aimed to determine the growth, production and prussic acid content of sorghum variety that planted on stylosanthes pasture with different harvesting time. This research was done using split-plot design with three replications which sorghum variety (brown midrib resistance (BMR) and Super-2) as the main plot and harvesting time (6, 8 and 10 weeks) as the sub plot. The sorghum seeds were germinated for 12 days before planted on the 30 days stylosanthes pasture which was planted with planting space 25 x 25 cm. Sorghum was planted with planting space 75 x 25 cm. The variables observed were plants height, dry and organic matter production and prussic acid. Data obtained were analyzed statistically using analysis of variance and significantly different between means were tested with Duncan's New Multiple Range Test  (DMRT). Sorghum BMR had plant height, dry and organic matter production higher (P<0.05) than Super-2. Prussic acid content of BMR was lower (P<0.05) than Super-2. The older harvesting time increase (P<0.05) plant height, dry matter and organic production, but reduced (P<0.05) prussic acid content from 727.34 mg/kg to 241.71 mg/kg. Based on the results it can be concluded that the oldest harvesting time (10 weeks) produced the highest dry and organic matter, and reduce prussic acid content. Sorghum BMR is more productive and grew faster than Super-2. Sorghum BMR that harvested in 10-week shows the best in growth and productivity also had lower prussic acid content.